The Effect of Process Factors on the Mechanical Properties of Styrene-NR Elastomers Containing Natural Rubber-Graft- Polystyrene - Tarinee Nampitch; Polchit Buakaew (Agriculture and Natural Resources, 2006)
Styrene-NR elastomers containing natural rubber-graft-polystyrene were prepared by an emulsion polymerization using potassium persulfate as an initiator. The effect of process factors on tensile strength was investigated by varying the temperature, rubber-to-monomer ratio, and initiator and emulsifier contents from 50 to 64 oC, 1.5 to 9, 0.8 to 1.4 g, and 4.5 to 6.5 g, respectively. Experimental results indicated that the tensile strength increased with an increase in reaction temperature, rubber to monomer ratio, and initiator and emulsifier contents.